Migrasi Magis Subjek Feyre dalam A Court of Throns And Roses Karya Sarah J. Mass - Luhfi, Muhammad; Jannah, Raudhatul; Dwi Jayanti, Nur Fadillah (Samsara Institute Publisher, 2025)
This study analyzes Sarah J. Maas's novel A Court of Thorns and Roses (2015) through the perspective of Jacques Rancière, specifically the concept of distribution of the sensible and subject migration. The focus of the study is directed at the transformation of the character Feyre Archeron who experiences a